Joint Effects of Synchronization Errors of OFDM Systems in Doubly-Selective Fading Channels. (29th January 2009) - Chin Chin, Wen-Long Wen-Long; Chen Chen, Sau-Gee Sau-Gee
Abstract : The majority of existing analyses on synchronization errors consider only partial synchronization error factors. In contrast, this work simultaneously analyzes joint effects of major synchronization errors, including the symbol time offset (STO), carrier frequency offset (CFO), and sampling clock frequency offset (SCFO) of orthogonal frequency-division multiplexing (OFDM) systems in doubly-selective fading channels. Those errors are generally coexisting so that the combined error will seriously degrade the performance of an OFDM receiver by introducing intercarrier interference (ICI) and intersymbol interference (ISI). To assist the design of OFDM receivers, we formulate the theoretical signal-to-interference-and-noise ratio (SINR) due to the combined error effect. As such, by knowing the required SINR of a specific application, all combinations of allowable errors can be derived, and cost-effective algorithms can be easily characterized. By doing so, it is unnecessary to run the time-consuming Monte Carlo simulations, commonly adopted by many conventional designs of synchronization algorithms, in order to know those combined error effects.